Financial Intermediation and the Creation of Macroeconomic Risks - Hans Gersbach (Center for Economic Studies and ifo Institute (CESifo), 2002)
We examine financial intermediation when banks can offer deposit or loan contracts contingent on macroeconomic shocks. We show that the risk allocation is efficient if there is no workout of banking crises. In this case, banks will shift part of the risk to depositors. In contrast, under a workout of banking crises, depositors receive non-contingent contracts with high interest rates while entrepreneurs obtain loan contracts that demand a high repayment in good times and little in bad times. As a result, the present generation overinvests and banks create large macroeconomic risks for future generations, even if the underlying risk is small or zero. This provides a new justification for capital requirements.
Keywords: 330; financial intermediation; macroeconomic risks; state contingent contracts; banking regulation